Collective Voluntary Pension Savings (APVC) in Chile (GESTIÓN Y TENDENCIAS, 2020)
Collective Voluntary Pension Savings (APVC) is a retirement savings option that allows organizations to promote pension saving among their workers. Together with Voluntary Pension Savings (APV) and Agreed Deposits (DC), APVC is one of the three instruments making up the voluntary savings pillar of the Chilean pension system. Although it was introduced by the 2008 pension reform, APVC has been little used. The aim of this article is to describe how it works, present figures on its development, and analyze the merits of its design in the context of the voluntary savings options offered by the Chilean pension system. The article concludes with a reflection on the possible causes of its low take-up and explores alternatives for promoting it.
Keywords: Collective Voluntary Pension Savings; APVC